Analisis Pertimbangan Hakim Kasus Putusan Ma Nomor 196 K/Pdt.Sus-Pailit/2017 Sema Mengatur yang Tidak Seharusnya - Gunawan Widjaja; Ririn Nurhidayanti (Bulletin of Community Engagement, 2024)
In 2016, PT Ramaldi Praja Sentosa, a company specializing in aircraft parts procurement and component repair, was rocked by a severe financial crisis. This crisis was triggered by the embezzlement of funds by one of its directors, leading to the company's inability to meet its financial obligations and ultimately filing for bankruptcy. The Central Jakarta Commercial Court rejected the petition due to the failure to meet the formal requirement of written consent from creditors as per the Supreme Court Circular Letter (Surat Edaran Mahkamah Agung) SEMA Number 2 of 2016. The Supreme Court then upheld this decision in cassation No. 196 K/Pdt.Sus-Bankruptcy/2017. This analysis delves into the reasons for the rejection of the bankruptcy petition, based on the provisions in Law No.37 of 2004 regarding Bankruptcy and Suspension of Payment (UUK-PKPU) and SEMA No.2/2016. It also underscores the implications of creditors' inactivity in providing consent to the bankruptcy mechanism. This case serves as a clear instance of the Supreme Court's overreach, as it issued SEMA with unnecessary guidance that is not in line with Law No.37 of 2004 regarding Bankruptcy and Suspension of Payment.